Peran Pendidikan Lingkungan Keluarga dalam Landasan Pendidikan pada Masyarakat Batak - Norde Norde; Dotrimensi Dotrimensi (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
In addition to helping Batak children succeed in formal education, family education plays an important role in shaping the character, cultural values, and identity of the Batak people. The philosophy of Anakkon Hi Do Hamoraon Di Au, which means Children are the wealth of life, is a life principle that has been embedded in the lives of the Batak people. Which reflects how important the role of children is in the Batak family and how education is the main investment for their future. The purpose of this study was to determine how family education functions as a foundation for education in Batak culture. A qualitative descriptive approach is the research methodology used. Based on the research findings, family-based education is a key component of the Batak community education framework.